Enunciados comunicativos de uma jovem usuária de comunicação alternativa e seus parceiros de comunicação - Silva, Aline Pillegi da (Universidade Federal de São Carlos, 2011)
Communication, innate and essential factor to human development, finds itself present in every moment of life. However, communication is not based just on speech, on orality. For a more efficient communication, we have facial and body expressions helping. For individuals who have no speech or speech is unintelligible, we can make use of Augmentative and Alternative Communication. The point of this study is to trace and analyze the profile of communicative statements of two young girls of thirteen years old, Marcela, cerebral palsy, literate, who not maintain oral function and uses alternative communication system, and Miriam, with normal development who uses speech to communicate (subject control). This research is part of a cross-cultural project that aims to describe how the understanding and expressing of certain kinds of utterances graphics occurs in children and young people of different ages and in different countries that uses alternative communication systems, and how these statements are understood by partners - parents, teachers and peers. The alternative system used by the participant with cerebral palsy consisted of pictures of family, words and sentences, alphabet and numerals in the format of a book of alternative communication. To collect data we used the following instruments: semi-structured interview with the mother, teacher, Marcela and Miriam; evaluation of the communication system held by Marcela`s mother and her teacher; standardized instruments for rating intelligence, receptive language, motor skills; communicative tasks applied to the two participants (comprehension tasks and production). Data revealed that the mother was the more competent communication partner, had more knowledge about the use of alternative communication system and favored the development of Marcela`s alternative language. Data also revealed that Marcela had no difficulties in comprehensive and expressive language, compared with his partner, Miriam. The main difference in the answers from Marcela and Miriam was about the response time. Marcela tok a longer time to give the answers, compared with Miriam. This is due to the fact of Marcela using augmentative and alternative communication to give the answers while Miriam uses speech. It can be concluded that individuals with impaired speech, with normal cognitive development, can communicate itself as effectively as individuals without impairment of speech, since the alternative communication system is implemented effectively and their communication partners are trained in the use of AAC.
Keywords: Educação especial; Comunicação alternativa; Parceiros de comunicação; Paralisia cerebral; Augmentative and Alternative Communication; Communication Partners; Cerebral Palsy; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL